Rapunzel syndrome - Altonbary, Ahmed Youssef (J Transl Int Med, 2015)
Bezoars are concretions of human or vegetable fibers that accumulate in the gastrointestinal tract. Trichobezoars are common in patients with underlying psychiatric disorders who chew and swallow their own hair. Rapunzel syndrome is a rare form of gastric trichobezoar with a long tail extending into the small bowel. This syndrome was first described in 1968 by Vaughan et al. and since then till date just 64 cases have been described in the literature. We present the only documented case with Rapunzel syndrome in Egypt.